2016
DOI: 10.7554/elife.12081
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis for ecological adaptation of the Atlantic herring revealed by genome sequencing

Abstract: Ecological adaptation is of major relevance to speciation and sustainable population management, but the underlying genetic factors are typically hard to study in natural populations due to genetic differentiation caused by natural selection being confounded with genetic drift in subdivided populations. Here, we use whole genome population sequencing of Atlantic and Baltic herring to reveal the underlying genetic architecture at an unprecedented detailed resolution for both adaptation to a new niche environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
233
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 164 publications
(252 citation statements)
references
References 93 publications
(128 reference statements)
18
233
1
Order By: Relevance
“…Spawning time and location of herring are affected by genetic factors (Martinez Barrio et al, 2016) supporting that NSS, CSS and Landvik herring might represent discrete populations. Even though no direct evidence for natal homing being essential for the discrete population concept exist in this thesis Paper II, there are some indications that fidelity of adult individuals to time and conditions of spawning resemble their own situation at the larval stage (Paper III).…”
Section: Population Structure Of Herring In Landvikvannet and Adjacenmentioning
confidence: 91%
See 4 more Smart Citations
“…Spawning time and location of herring are affected by genetic factors (Martinez Barrio et al, 2016) supporting that NSS, CSS and Landvik herring might represent discrete populations. Even though no direct evidence for natal homing being essential for the discrete population concept exist in this thesis Paper II, there are some indications that fidelity of adult individuals to time and conditions of spawning resemble their own situation at the larval stage (Paper III).…”
Section: Population Structure Of Herring In Landvikvannet and Adjacenmentioning
confidence: 91%
“…This variety is, in theory, a good prerequisite when studying the population structure of herring, because genetic differentiation might arise based on isolation-by-distance (Wright, 1965) or environmental differences leading to phenotypic variation. Phenotypic differences of Atlantic herring have been well studied (see e.g., and recent studies also suggested genetic differentiation between populations Martinez Barrio et al, 2016). However, herring populations are often highly migratory and undertake long-distance migrations from a few 100 km to more than 1000 km between feeding, overwintering, and spawning areas.…”
Section: Life History Of Atlantic Herringmentioning
confidence: 99%
See 3 more Smart Citations